An anatomical study of the superficial palmar communicating branch between the median and ulnar nerves. (February 2016) - Sulaiman, S.; Soames, R.; Lamb, C.
The palmar communicating branch between the median and ulnar nerves was investigated in 98 hands with the aim of outlining its most common branching patterns and describing its relationship to well-defined anatomical landmarks, including the bistyloid line, wrist crease and flexor retinaculum. Five branching patterns were identified and classified based on their proximal and distal attachments. The palmar communicating branch was found to lie between 26%–79% of the total distance between the metacarpophalangeal joint of the long finger and the wrist crease, and 35%–75% of the total distance between the metacarpophalangeal joint of the long finger and the middle of the bistyloid line. With the aid of the morphometric indices obtained from this study, a risk area where the palmar communicating branch is most likely to be found is outlined. Knowledge of the branching patterns and location of the palmar communicating branch can help clinicians to better assess variations in the patterns of sensation, preserve the nerve during surgical interventions to the palm and better assess post-operative complications involving the branch.